Inhibitory effects of quercetin and its major metabolite quercetin-3-O-β-D-glucoside on human UDP-glucuronosyltransferase 1A isoforms by liquid chromatography-tandem mass spectrometry - Zhang, Rui (Exp Ther Med, 2021)
Quercetin is a flavonoid that is widely present in plant-derived food. Quercetin-3-O-β-D-glucoside (Q3GA) is a predominant metabolite of quercetin in animal and human plasma. The inhibitory effects of the UDP-glucuronosyl transferases (UGTs) caused by herbal components may be a key factor for the clinical assessment of herb-drug interactions (HDIs). The present study aimed to investigate the inhibitory profile of quercetin and Q3GA on recombinant UGT1A isoforms in vitro. The metabolism of the nonspecific substrate 4-methylumbelliferone (4-MU) by the UGT1A isoforms was assessed by liquid chromatography-tandem mass spectrometry. Preliminary screening experiments indicated that quercetin exhibited stronger inhibitory effects on UGT1A1, UGT1A3, UGT1A6 and UGT1A9 enzymes than Q3GA. Kinetic experiments were performed to characterize the type of inhibition caused by quercetin and Q3GA towards these UGT isoforms. Quercetin exerted non-competitive inhibition on UGT1A1 and UGT1A6, with half maximal inhibitory concentration (IC(50)) values of 7.47 and 7.07 µM and inhibition kinetic parameter (K(i)) values of 2.18 and 28.87 µM, respectively. Quercetin also exhibited competitive inhibition on UGT1A3 and UGT1A9, with IC(50) values of 10.58 and 2.81 µM and K(i) values of 1.60 and 0.51 µM, respectively. However, Q3GA displayed weak inhibition on UGT1A1, UGT1A3 and UGT1A6 enzymes with IC(50) values of 45.21, 106.5 and 51.37 µM, respectively. In the present study, quercetin was a moderate inhibitor of UGT1A1 and UGT1A3, a weak inhibitor of UGT1A6, and a strong inhibitor on UGT1A9. The results of the present study suggested potential HDIs that may occur following quercetin co-administration with drugs that are mainly metabolized by UGT1A1, UGT1A3 and UGT1A9 enzymes.